2011, un año de récords en la Olimpiada Peruana de Química (OPQ) - Chong, Miguel (Pontificia Universidad Católica del Perú, 2011)
The Peruvian Chemistry Olympiad (OPQ) set a new participation record, with over 2,000 students nationwide. Furthermore, the Peruvian National team achiev edits greatest success in the International Chemistry Olympiad (IChO) and the Iberoamerican Chemistry Olympiad (OIAQ), with a total of seven awards.

La Olimpiada Peruana de Química (OPQ) ha logrado el récord de participación con cerca de 2,000 estudiantes a nivel nacional. Además, el equipo peruano ha conseguido sus mayores éxitos en la Olimpiada Internacional de Química (IChO) y en la Olimpiada Iberoamericana de Química (OIAQ), con un total de 7 galardones.
2011, a year of records in the Peruvian Chemistry Olympiad (OPQ)
Keywords: Química; https://purl.org/pe-repo/ocde/ford#1.04.00